Isolation and characterization of Salmonella enterica from Antarctic wildlife - Vigo, Germán Blas; Leotta, Gerardo Aníbal; Caffer, M. I.; Salve, Angela; Binsztein, Norma; Pichel, Mariana (2010)
In recent years, the human presence in Antarctica has increased and as a consequence, the possibility of microorganisms’ introduction. The aims of this work were to determine the presence of Salmonella enterica in Antarctic seabirds and sea mammals, to characterize the isolates identified, and to determine the genetic relation of Antarctic S. enterica isolates among them and compare with isolates of human, animal, and food sources recovered in Argentina. During the summer 2000 and 2002 in Potter Peninsula, and during the summer 2001 and 2003 in Hope Bay, a total of 1,739 fecal samples from Antarctic animals were collected and analyzed. In summer 2000, S. Newport and S. Enteritidis were isolated from 8.9% of southern giant petrels ( Macronectes giganteus ). In summer 2003, S. Enteritidis was isolated from 1.5% of Adelie penguins ( Pygoscelis adeliae ), from 5.5% of skuas ( Stercorarius sp.), from 5.4% of kelp gulls ( Larus dominicanus ), and from 5.6% of Weddell seals ( Leptonychotes weddelli ). All the isolates belonging to the same serovar showed indistinguishable genomic profiles by Pulse-Field Gel Electrophoresis (PFGE) with Xba I and Bln I restriction enzymes and by Random Amplified Polymorphic DNA (RAPD-PCR). In addition, these Antarctic strains were different from S. enterica isolates from different sources identified in Argentina during the same or close time periods. Facultad de Ciencias Veterinarias